Comparative Study of Economic Crisis in Nigeria: Lessons from Economic Crisis in Other Developing Countries - Utami, Anisa Fitria; Miranda, Mira (West Science Accounting and Finance, 2024)
This comparative study explores the economic crisis in Nigeria, drawing lessons from economic crises in other developing countries. Through a comprehensive literature review, the study examines the root causes, impacts, and recovery strategies associated with economic downturns in regions with similar socioeconomic conditions. Key factors such as political instability, poor governance, and over-reliance on a single economic sector are identified as primary contributors to economic crises. The analysis of case studies from Latin America, Asia, and Africa highlights successful policy interventions and adaptive measures that have facilitated economic recovery in these countries. The findings underscore the importance of economic diversification, robust financial regulations, and proactive government policies in mitigating the effects of economic crises. Recommendations for Nigeria include strengthening governance, reducing corruption, diversifying the economy, enhancing financial regulations, and implementing proactive government policies to enhance economic resilience and stability.